Bullous Pemphigoid Occurring after Stopping Imatinib Therapy of CML: Is a Continuation of Post-Treatment Follow-Up Needed? - Alexander Yakobson; Ala Eddin Neime; Omar Abu Saleh; Kayed Al Athamen; Walid Shalata (Clinics and Practice, 2023)
Advancements and the use of tyrosine kinase inhibitors (TKIs) have revolutionized the treatment of Chronic Myeloid Leukemia (CML), achieving unprecedented success rates and expanding their applications to various neoplasms. However, the use of TKIs is not without its drawbacks. Skin, gastrointestinal, and central nervous systems are particularly susceptible to adverse effects, including a higher incidence of autoimmune responses in treated individuals. In this report, we present a unique case of bullous pemphigoid, a rare autoimmune disease, which has not been previously associated with TKI therapy as an adverse effect, particularly appearing after discontinuing Imatinib® treatment.